Does She Kill Like He Kills?: comparison of Homicides Committed by Women with Homicides Committed by Men in Spain - Santos-Hermoso, Jorge (European journal on criminal policy and research, 2023)
The homicides committed by women make up between 5 and 15% of the total number of homicides recorded in the world. Studies based on the gender of the perpetrator have been uncommon due to the low level of prevalence of female homicide offenders, but this tendency is currently undergoing a change. Nonetheless, in general, there is still limited knowledge of the role of women in serious crime, which makes the task of criminal policy more difficult. Therefore, the present investigation seeks to perform a comparative analysis of the homicides committed by women (n = 56) with those committed by men (n = 521). The cases in this sample correspond to homicides solved in Spain by the Civil Guard between the years 2013 and 2018. The findings of the study show that homicides by women have distinctive characteristics, with 3 out of every 4 taking place in the family environment, and these being dominated by cases of filicide. The victims are underage males with some type of vulnerability and a mental disorder. The female perpetrators tend to have a partner and live with somebody, have a mental disorder and do not present a prior criminal record. With regard to the crime, homicides perpetrated by women take place in the afternoon, without witnesses and in residences; when it comes to the criminal behaviours, they use weapons of opportunity, above all asphyxiating methods, they alter the scene and do not flee from the scene of the crime.